Association Between Pancreatic Cystic Lesions and High-grade Intraepithelial Neoplasia and Aging: An Autopsy Study. Issue 8 (September 2019) - Matsuda, Yoko; Kimura, Wataru; Matsukawa, Miho; Aida, Junko; Takubo, Kaiyo; Ishiwata, Toshiyuki; Furukawa, Toru; Mino-Kenudson, Mari; Arai, Tomio
Abstract : Objectives: This study aimed to clarify clinicopathological features of pancreatic cysts. Methods: Pancreata from 280 autopsies (median, 83 years; male, 146; female, 134) were sectioned every 5 mm. Cysts (<10 mm) were diagnosed as a simple cyst or low-grade, intermediate-grade, or high-grade dysplasia. Results: We found 236 cysts in 93 patients (33.2%). The number and diameter of cysts increased according to the age. Of the 236 cysts, 9 (3.8%) were with high-grade dysplasia. Cysts with high-grade dysplasia arose in the pancreata of older patients with larger numbers of cysts. In contrast, 15 noncystic lesions with high-grade dysplasia were also detected. Hence, in total, 24 high-grade dysplastic lesions in 15 patients (5.4%) were noted. Of the 15 patients with high-grade dysplastic lesions, in 10 patients, the condition was accompanied by pancreatic cysts, whereas 5 patients did not have any cysts in the pancreas; therefore, patients with cyst showed higher incidence of high-grade dysplasia (10.8%; P = 0.0047) than patients without cyst (2.7%). All cysts with high-grade dysplasia were located in the branch duct of the pancreatic head/body, whereas 20% of noncystic lesions with high-grade dysplasia were located in the main pancreatic duct. Conclusions: Cystic lesions with high-grade dysplasia may have different characteristics compared with noncystic high-grade dysplasia.